Groundwater Recharge from Agricultural Areas in the Flatwoods Region of South Florida - Sanjay Shukla; Fouad H. Jaber (EDIS, 2006)
ABE-370, a 7-page illustrated fact sheet by Sanjay Shukla and Fouad H. Jaber, defines recharge, discusses factors affecting it and methods to estimate it, and discusses the results from a study that investigated recharge from an agricultural area in south Florida. Includes references. Published by the UF Department of Agricultural and Biological Engineering, July 2006.